2022
DOI: 10.37227/jibm-2022-01-5293
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Inclusion Experience of Trans Workers: The Missing Link of Trans-Friendly Environment in Organizations

Abstract: The transgender community, one of the most marginalized communities, faces a range of discriminatory issues in workplaces and educational institutions. The study seeks to investigate the extent of organizational support ensured by the workplaces to create a transgender-friendly environment in Bangladesh. The paper opted for a mixed study and surveyed 47 trans workers using a questionnaire. The responses yielded quantitative data that was analyzed using SPSS. The qualitative data was collected through focus gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…J. Lee (2021) also echoed that such communities were treated with hostility and ignorance from all corners of Pakistan. Hafiz et al (2022) revealed that since the economic productivity of a developing country can enhance if the number of individuals in the workforce grows relative to the number of dependents, the inclusion of the trans-community can contribute to the country's existing demographic dividends. During the COVID-19 pandemic, trans-participants shared their resilience stories, identifying how prior preparation fostered resilience; radical acceptance was a source of resilience (Aberu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…J. Lee (2021) also echoed that such communities were treated with hostility and ignorance from all corners of Pakistan. Hafiz et al (2022) revealed that since the economic productivity of a developing country can enhance if the number of individuals in the workforce grows relative to the number of dependents, the inclusion of the trans-community can contribute to the country's existing demographic dividends. During the COVID-19 pandemic, trans-participants shared their resilience stories, identifying how prior preparation fostered resilience; radical acceptance was a source of resilience (Aberu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A more diverse workforce can be a potential source of strength for a company as through this tool, they can enhance their understanding of the diverse needs of diverse sets of customers. According to Hafiz et al (2022), such achievement can effectively predict organizational sustainability.…”
Section: Implications Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…They are isolated from mainstream society, stigmatized, subdivided, mistreated, and marginalized (Hosain et al, 2002; Hossain, 2010; Jalil, 2012). On the other hand, transgender people in Bangladesh are looked down upon as though they are not human beings and are treated brutally only because they do not have the gender identity approved by the society or the government (Jebin & Farhana, 2015; Islam, 2019; Sema & Islam, 2020; Abedin & Sarker, 2022; Sifat & Shafi, 2021; Hossain & Ferdous, 2020; Fontana, 2020; Safa, 2016; Hafiz et al, 2022). PWD and TG people are jeopardized to their personal, family, and social life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their social, economic, cultural, and political participation is not recognized (Sifat & Shafi, 2021). They are mysterious to the common people (Sema & Islam, 2020) and they are facing a range of discriminatory issues in workplaces and educational institutions (Hafiz et al, 2022). Because of the negative attitude of the people and limited livelihood options, they isolate and hide them from the mainstream society (Hossain & Ferdous, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%